Perancangan Ulang Ruang Pamer Dan Fasilitas Publik Di Museum Seni Rupa Dan Keramik Jakarta Dengan Pendekatan Interaktif - Asmatia Mahardhika, Latifa; Adli Wismoyo, Erlana; Bayu Perdana, Aditya (Telkom University, 2024)
The Jakarta Fine Arts and Ceramics Museum is an art museum in Jakarta which is a Dutch heritage building so it is classified as a type A cultural heritage building. According to Government Regulation no. 66 of 2015 concerning museums, museums are institutions whose function is to protect, develop, utilize collections and communicate them to the public. Although Government Regulations tend to pay attention to the collection aspect, the ICOM definition emphasizes visitor service and involvement, an aspect that is still poorly implemented in several museums in Indonesia. The Fine Arts and Ceramics Museum, which has various kinds of collection objects, still uses old standard display media so that the objects on display are not well appreciated and do not meet the standards. In this case, it is important to evaluate the presentation of collections and public facilities in accordance with existing standards. Therefore, with the redesign using an interactive approach, it is hoped that it can increase the public's attraction to visit, supported by attractive display media and interactive activities in the museum. This effort is expected to provide an interesting experience for visitors, increase understanding of art and culture, and strengthen the role and vision and mission of the museum as a center for education, recreation and community reflection. Keywords: art museum, ceramics, interactive, display